2013
DOI: 10.1186/1471-2458-13-33
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency among healthy adolescents in Al Ain, United Arab Emirates

Abstract: BackgroundAlthough vitamin D deficiency has been studied in various adult populations, there are few data on the prevalence of this nutritional deficiency among healthy adolescents in the United Arab Emirates (UAE). This study was conducted to determine the prevalence of vitamin D deficiency and to examine its correlates in adolescents aged 15 to 18 years.MethodsThis was a cross-sectional study in urban schools. Healthy adolescents (N=315) from a sample of 8 schools were randomly selected from the 142 schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 28 publications
6
88
0
5
Order By: Relevance
“…UAE in spite being a sunny subtropical country, with maximum span of summer in all seasons, is now widely known to have comparable vitamin D deficiency as other part of globe [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UAE in spite being a sunny subtropical country, with maximum span of summer in all seasons, is now widely known to have comparable vitamin D deficiency as other part of globe [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this problem is not only confined to the adult population. A study conducted among the adolescents in Al Ain city (UAE), showed prevalence of vitamin D < 30ng/ ml of 65%, the lower percentage could be explained by longer sun exposure at school age [9].…”
Section: Introductionmentioning
confidence: 99%
“…The review also showed that studies that reported changes in quality of life as a result of vitamin D supplementation were in clinical populations on shortterm vitamin D. Most articles reviewed displayed poor methodological quality (e.g. no randomization/blinding, dropout description, or vitamin D assessment) (Mithal and Kaur, 2012;Muhairi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 86% of these subjects with multiple risk factors were vitamin D deicient. Several studies have reported Vit D deiciency among diferent populations from the Middle East [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%